Practitioner Profile: An Interview with Christine Moriarty - Christine Moriarty (Journal of Financial Therapy, 2018)
Christine Moriarty, MBA, CFP® is a financial speaker, author and coach. She has been quoted extensively in publications including USA Today, Good Housekeeping, the "Boston Globe" and "Fidelity Focus Magazine," as well as several books including "Living Your Joy." She is a past columnist for Vermont Woman and has been published in several periodicals and on-line publications. In addition, she writes a monthly newsletter, “My Peace on Money,” that reaches a growing list of thousands of subscribers.